Regional glacial isostatic adjustment modeling: integration of geodetic, geophysical and geological data - Linsalata, Fernando <1991> (Alma Mater Studiorum - Università di Bologna, 2024)
The Earth is always on the move, constantly. In the last millions of years the Earth's climate has followed a cycle of alternating glacial and interglacial conditions, with a periodicity of the order of 100 kyr. The most recent cycle began approximately 110 kyr ago and reached the Last Glacial Maximum at approximately 20-26 kyr before present . As a result, the average sea-level was about 125-130 m lower than at present and large regions, now covered by shallow seas, were dry land in places forming bridges between islands. Though the ice melted long ago, the land once under and around the ice is still rising and falling in reaction to ice burden. This ongoing movement of land is called Glacial Isostatic Adjustment (GIA) and represents the response of the solid Earth to mass redistribution during a glacial cycle, that is describes the viscoelastic response of the solid Earth to time-dependent changes in ice and ocean loading over the course of a glacial-interglacial cycle. In the first part of this work the impact of the GIA process in the Mediterranean basin will be analyzed, with particular attention to the Venice Lagoon, where the sea-level variations could be catastrophic if we consider the current effect of climate changes. The second piece of work is on the study of the strength of the lithosphere beneath Graham Land region (Antarctic Peninsula) using numerical modeling which simulate lithospheric deformation as a function of geological and geophysical parameters. Although these two works might seem disconnected, the study of the rheology and strength of the lithosphere play an important role in GIA modeling. Indeed, increasingly advanced knowledge of the crustal and upper mantle rheological structure will lead to better understanding the geological processes but also to better constrain geophysical processes such as GIA.